A pH-responsive fluorescent [5]pseudorotaxane formed by self-assembly of cationic water-soluble pillar[5]arenes and a tetraphenylethene derivative1. Issue 61 (7th August 2015) - Chen, Rener; Jiang, Huajiang; Gu, Haining; Zhou, Qizhong; Wu, Jiashou; Chen, Dingben; Zhang, Jie
<x xml:space="preserve">Abstract</x> The formation of a pH-responsive fluorescent [5]pseudorotaxane by self-assembly of cationic water-soluble pillar[5]arenes and a tetraphenylethene derivative was reported.